Development of a Cross-Platform Application for Islamic Inheritance Distribution Calculation Using Python and Streamlit - Iqbal, Taufiq; Bahruni, Bahruni; Al-Bahri, Fauzan Putraga (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This research describes the development of a cross-platform Islamic inheritance calculation system using the Streamlit framework with Python. This study aimed to create an accessible digital tool that accurately calculates inheritance distribution according to Islamic law (faraid), as mandated in Surah An-Nisa (verses 11–12). A Research and Development (R&D) approach was employed in this research, utilizing a prototyping model, where the system was designed through several iterative stages: analysis, design, implementation, and testing. The resulting application integrated modular architecture separating business logic from user interfaces and validation layers for flexibility maintainability as well as platform independence. Testing on various scenarios confirmed 100% accuracy in calculating shares of six main heirs—husband wife father mother son and daughter validated against manual computations and computations based on fiqh. The application runs without additional installation requirements on Windows macOS Linux plus mobile browsers supported by responsive design plus real-time validation. Although the system has high accuracy plus usability it is limited to basic cases since advanced inheritance mechanisms such as aul radd or hijab are not included in this version. Future development is suggested to increase categories for heirs enable data storage provide educational content and integrate AI-assisted features for complex case analysis. In general, this study contributes to the digital transformation of Islamic law applications which promote accessibility transparency and computational precision in managing inheritances.